Back to basics -vc - UMP, PNC
Universiti Malaysia Pahang (UMP) Vice-Chancellor, Professor Dato’ Dr. Daing Nasir Ibrahim delivered his new year speech for 2013 by making a call to all staff to continue to build success and to revisit the basis of the strategic implementation phase in a move to continue keep on building excellence.